Smart home microcontroller: Telephone interfacing - Leong, , CS; Goi,, BM (2006)
In this paper, we present the results of the effort to design and produce a smart home system, PhoneTech. PhoneTech has been designed and built utilizing the telephone network to enable users to remotely control an array of automated home electronic devices by entering a series of commands through phone. The aim of PhoneTech is to provide the users with a better home life experience without overpowering them with complex technologies while keeping the home life as normal as possible.